Word бізнес as an object and subject in Soviet and post-Soviet journalism - Любавська, Юлія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article traces potential of compatibility of verbs with the word business in journalistic texts of the Soviet (the second half of the XX th century) and post-Soviet periods. It is revealed that in modern texts in such phrases lexeme business is used in direct and analogical meaning, while in the Soviet ones this word is almost never used in analogical meaning. It was determined that in Soviet journalism verbs which go with this word are stylistically neutral, but operate in the context with negative evaluation. In modern ones they are mostly metaphorical and in such expressions business is conceptualized as a victim. However, in the text where the lexeme is used in a subjective function business often appears as an all-powerful giant.